Blood DNA methylation of CRF and its association with amygdala volume and mood in Cushing’s syndrome - Lee, Richard S.; Santos, Alicia; Garrison-Desany, Henri; Aulinas, Anna; Carey, Jenny L.; Vives-Gilabert, Yolanda; Cox, Olivia H.; Cuilan, Gabriel; Webb, Susan M.; Resmini, Eugenia (Frontiers in Epigenetics and Epigenomics, 2024)
Objective: The impact of chronic exposure to stress or glucocorticoids on psychiatric symptoms has been exemplified by cases of iatrogenic or endogenous hypercortisolism such as Cushing's syndrome (CS). The amygdala plays an important role in mediating both stress and affective responses, and one of the key factors that link stress response and psychiatric symptoms is the corticotropin-releasing factor (CRF). Epigenetic changes, especially those occurring on CpG dinucleotides in DNA of glucocorticoid target genes in blood, have been previously implicated as potential predictors of glucocorticoid-related events in the central nervous system (CNS). In this study, we examined amygdala volume and mood symptoms in CS patients and aimed at evaluating whether these parameters were associated with blood DNA methylation of CRF.Methods: In this cross-sectional study, 32 CS patients and 32 healthy controls matched for age, sex, and years of education underwent an MRI scan, a Beck Depression Inventory-II, and a State-Trait Anxiety Inventory. Genomic DNA extracted from total leukocytes were used for DNA methylation analysis of several CpG dinucleotides at the CRF promoter region.Results: Significant associations between CRF methylation vs. amygdala volume (CpG-1, P=0.006) and depression scores (CpG-2, P=0.01) were found. To assess whether the promoter CpG methylation has functional consequences, we examined RNA and DNA extracted from non-CS, postmortem amygdala tissues. A significant association between CpG methylation and gene expression (CpG-1, P=0.004) was observed.Conclusion: These results demonstrate that methylation levels of the CRF promoter CpGs are associated with amygdala volume in CS and related mood symptoms. Methylation levels may also be associated with CRF expression. This finding supports the feasibility of using epigenetic patterns in blood as a surrogate for assessing GC-related pathologies in the brain.